Role of NF-kB transcription factors, cell-cycle regulators and apoptotic genes in proliferation of MCF-7 cells - SHUBHA M. HEGDE; NAVEEN KUMAR M; K. MANJUNATH; S. CHIDANANDA SHARMA (International Journal of Pharma and Bio Sciences, 2017)
The cross-talk between steroid hormones and their classical nuclear receptors (NRs) play a major role on the development and progression of breast cancer. In a non-classical genomic pathway, hormone-receptor complex tether to transcription factors (TFs) such as activator protein-1 (AP-1) or nuclear factor-kappa B (NF-kB) and mediate transcription of target genes involved in breast cancer progression. MCF-7 cells treated with steroid hormones alone/in combination and steroid hormones in combination with their antagonists were used as in vitro model system in the present study. Direct cell counting assay showed that E2 increased cell proliferation with time. The semi qRT-PCR showed that steroid hormones alone increased the mRNA levels of NF-kB TFs, Cyclin D1, Cyclin E1, E2F1 and Bcl2 by more than 1-fold and decreased p53, p21 and Rb mRNA levels by more than 20%. The steroid hormone antagonists ICI 182,780 and RU486 decreased the mRNA levels of NF-kB TFs, Cyclin D1, Cyclin E1, E2F1 and Bcl2 by more than 35% and increased the levels of mRNAs of p53 and Rb by 1-fold and Bax by more than 26%. Results of the present study suggested that steroid hormones probably tether to NF-kB TFs and upregulate cyclins and E2F1 genes which culminate in the increased proliferation. Thus ERa/NF-kB/E2F1 pathway serves as an important target in the therapeutic modality for treating triple positive breast cancer cells.